APLIKASI PENGIDENTIFIKASI VERBA PERFEKTIF BAHASA ARAB - Zuhriah Zuhriah; Najmuddin H. Abd Safa; Ikhwan M. Said; Yusring Sanusi Baso (Nady Al-Adab : Jurnal Bahasa Arab, 2021)
This article describes the application of grammar rules in computation system with the object of study ofArabic perfect verbs. The application of grammar rules in a system is very significant to do because thestatistic model used in the previous application has not given a good result yet. A system must havegrammar rules in identifying each verb-forming component in order to achieve a precise and accurateresult. Therefore, this application used tagmemic grammar in identifying Arabic perfect verbs .The method used was mixed methods as this research is based on research and development (R and D) –research used to produce a specific product and to examine the effectiveness of the product. Thismethod began with needs analysis and literature review related to grammar, theory implementation,application planning, product evaluation, validation and dissemination .The result showed that the system has been able to identify perfect verbs in a sentence based on its signs.In addition, the system has also been able to elaborate the verbs into core tagmeme and outer coretagmeme based on tagmemic theory .